The modern state and directions of small enterprises in Poltava oblast - Помаз, Ю. В. (Scientific Progress & Innovations, 2012)
The modern state is investigated in the article, the dynamics of basic indices of small enterprises development in Poltava oblast is analysed. Activity of local-authority is examined in relation to the increasing efficiency of small enterprises activity. The problems of small enterprises development in Poltava oblast are revealed. The directions of these problems decisio are defined. The small enterprise sector, as the meaningful element of development of market economy of Poltava oblast grows into an important stabilizing factor, possible mean of solving complicated economic and social problems.